Global wage report 2010/11 : wage policies in times of crisis. (International Labour Office, 2010)
The second in a series of ILO reports focusing on wage developments, this volume reviews the global and regional wage trends during the years of the economic and financial crisis of 2008 and 2009. In Part I, the report highlights the slow down in the growth of monthly average wages as well as some short-term fluctuations in the wage share. These changes happened against a backdrop of wage moderation in the years before the crisis and a long-term trend of rising wage inequality since the mid-1990s. Part II of the report discusses the role of wage policies in times of crisis and recovery. Collective bargaining and minimum wages can help achieve a balanced and equitable recovery by ensuring that working families share in the fruits of future economic growth. At the same time, preventing the purchasing power of low-paid workers from falling can contribute to a faster recovery by sustaining aggregate demand. The report shows that policy strategies and design are crucial to ensure that low-paid workers benefit from union representation and minimum wages, and argues that wage policies must be complemented with carefully crafted in-work benefits and other income transfers. Part III concludes with a summary of the report and highlights issues that are critical for improving wage policies.